2015
DOI: 10.1155/2015/762121
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation concerning Metals Bioavailability in Waters of Aries River Catchment by Using the Diffusive Gradients in Thin Films Technique

Abstract: The paper presents the metals content and bioavailability in waters of Aries River catchment, Romania. Concentration of labile dissolved metal species measured by diffusive gradients in thin films technique (DGT), metals in colloidal and in particulate phases, and also general physical-chemical indicators of water were determined. Very high total metal concentrations were found in the tributaries that drain the mining areas. However, the influence of the polluted tributaries on the Aries River water quality wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Generally, a high quantity of fertilizers and copper-based substances are used for vineyard growth. The interference between soil and vine-shoots produces the adsorption of metals and their binding to the organic part [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a high quantity of fertilizers and copper-based substances are used for vineyard growth. The interference between soil and vine-shoots produces the adsorption of metals and their binding to the organic part [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity is influenced both by total concentration and by availability of element [ 16 , 17 ]. Consequently, environmental regulations should include along the total elements thresholds, the evaluation of risk exposure to toxic elements in terms of their availability.…”
Section: Introductionmentioning
confidence: 99%
“…The total dissolved solids (TDS) were Over the years, several remediation measuRes. were taken, but the resulting wastes of the long periods of mining activities and their poor management have led to a significant deterioration of the quality of the natural environment [9,10,27,28].…”
Section: Sampling and Analytical Proceduresmentioning
confidence: 99%
“…The Aries River presents a higher vulnerability due to mining activities [8]. The main pollutants of the Aries River are Cu, Pb, Zn and cyanides, due to the acid mine drainage in the mining centers situated along the Aries River [8][9][10]. Different studies on the Aries River catchment revealed that the areas near the mining centers are still highly polluted and implicitly affected [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation